Rehabilitation care workers perceptions of the outcomes of a pilot training programme - Clark, Graham (Department of Health and Rehabilitation Sciences, 2015)
The South African National Development Plan (NDP) (National Planning Commission, 2011, p. 1) provides the road map for a reformed public health system by 2030. The proposed health system will be facilitated by, amongst others, training an appropriate balance of healthcare professional s including a cadre of community health workers (CHWs) that have a broad skills mix suited to reaching a larger number of people with first level intervention. With this in mind, a pilot group of CHWs were up-skilled as Rehabilitation Care Worker s (RCWs). The training program was a joint project between the Division of Disability Studies and the Departments of Occupational Therapy, Physiotherapy and Speech and Language Therapy at UCT. Problem: Little is known about the perspectives of RCWs on the benefits and challenges of additional training in rehabilitation and disability related skills. Rationale: To inform the curriculum for a rehabilitation care worker (RCW) training program and the Western Cape Department of Health (WCDoH) of ways in which this cadre of worker could contribute to the realization of the 2030 Healthcare Plan. Aim: To describe the outcomes of a pilot RCW training program from the perspective of the pilot group of graduates. The objectives were to identify the areas of practice where RCWs feel competent/incompetent, to identify aspects of the health services where RCWs believe they can contribute the most/the least and to identify the facilitators/barriers they experienced when deployed in the health field. Methodology: A qualitative descriptive study was conducted. Method: Focus groups were carried out with three groups of six participants. Findings: The plot that permeated the participants’ perspectives revolved around how the RCWs were pioneers in breaking new ground for the Western Cape Department of Health (WCDoH). Two themes informed the plot: "we move health services to a new level" and "we manage change in new ways". Discussion: It is argued that the pilot RCW curriculum achieved its’ objective of equipping a cadre of worker with basic rehabilitation, care and disability inclusion skills. While the envisaged role of RCWs in the health service and in making the NDP a reality is supported, it is argued that attention needs to be given to supervision structures and to training of all other health workers in order to promote inter professional practice. Conclusions: The pilot group of RCWs believe that they have acquired a new and large variety of skills that have enabled them to make a broad and positive impact in their places of work, at home and in the broader community.